HomeNetSec: enhancing home network security by Suricata Intrusion Detection System using Raspberry PI / Ahmad Shariff and Abidah Mat Taib - Shariff, Ahmad; Mat Taib, Abidah (College of Computing, Informatics and Media, UiTM Perlis, 2023)
Most of home network user are not aware that they can be exposed to attacks from threat actors through the Internet. It is important to educate the general public about home network security. So, this project aims to develop a low-cost network monitoring system. A preliminary survey was done to find the needs from the general publics. From the survey, there is a need for system that can enhance home network security and the finding of the survey was to create the HomeNetSec system. Result of functionality testing is the system can detect suspicious network traffic and bad network traffic. Each of the component of the system such as Suricata, Elasticsearch, Kibana and Fluent Bit functioned correctly. During usability testing, the users have evaluated that the system satisfied their needs of a system that can enhance their home network security.